Analisis Faktor-Faktor Yang Mempengaruhi Minat Masyarakat Mengunjungi Wisata Halal Sumatra Barat (Studi Kasus Wisatawan Muslim Milenial Indonesia) - Cupian Amzal; Annisa Rahmadita; Sarah Annisa Noven (ITB AAS INDONESIA Surakarta, 2021)
This study aims to determine and to analyse the factors that influence the intention of millennial muslim tourists travelling halal tourism in West Sumatra. Halal Tourism has developed rapidly and might become a world trend if the Covid-19 pandemic doesn’t occur. Halal tourism provides tour services and facilities not only for Muslim tourists but also for nonmuslim tourists. In 2016, Indonesia won 12 out of 16 categories on World Halal Tourism Award that makes Indonesia dominating the presentation, thus making Halal Tourism a potential sector to be developed. Four hundred millennial muslim tourist respondents were sampled; namely, those aged 20-40 years and had visited halal tourism in West Sumatra. The research was conducted using a descriptive quantitative approach and using a questionnaire that applied a Likert scale. The data obtained were analyzed employing the binary logistic regression method. The results indicated that the factors of knowledge, travel motivation, accommodation, the ease of obtaining halal food and drinks have a significant effect on the intention of millennial muslim tourists travelling halal tourism in West Sumatra. In contrast, the factors of electronic word of mouth, destination image, and facilities have no significant effect related to this concern.